The Analysis of The Influence of Work Motivation Level and Work Environment Conditions on Employee Performance - Winanti; RAHMAT AGUSTIAN, WAHID; Mawarida, Apriliani; Hermawati, Lusi; Farhan, Akhmad; Mendrofa, Yeremia; Singgih, Eman; Sopyan, Dedi; Sestri Goetjahjanti, Francisca; Hasna, Shofwatun (PT. BERBAGI TEKNOLOGI SEMESTA, 2024)
Low work motivation and non-conducive work environment often occur in various companies. Low motivation due to poor work system, compensation and work climate. This study aims to determine the effect of work motivation and work environment on employee performance at PT Surya Shueen Yueh Industry, which became the population and sample in this study were all employees with a sample of 60 people. The data used is primary data by distributing questionnaires. Data processing techniques through validity, reliability, normality, multicollinearity, heteroscedasticity, correlation coefficient and multiple regression tests. Based on the results of the study, work motivation and work environment partially affect employee performance. Simultaneously, work motivation and work environment also have a positive effect on employee performance. The contribution of this research is that it is hoped that the company can properly maintain the needs of employees in the company, this form of maintenance can be in the form of providing compensation according to the rules, health facilities, vacations, bonuses and other facilities. So that employees will feel at home to stay in the company and can work enthusiastically so that company targets can be achieved.